(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The life cycles of these species take place with the participation of intermediate hosts, the role of which is performed by various invertebrates (woodlice, mollusks, doge worms, etc.).). The number of these invertebrates in different biotopes fluctuated greatly depending on environmental factors. Significant fluctuations were observed in the daily rhythms of their activity. In this regard, it is of no small importance for the completion of the life cycles of the noted helminths withthe storage of theviability of their eggsinbiocenoses.